Les moments liminaires de la violence civique : un enjeu sociétal - Emmanuelle Jégo / Ghislaine Jay-Robert (Cahiers des Études Anciennes)
This introduction puts emphasis both on the importance to study the place of violence in a society to better understand it, and on the difficulty of doing so. This difficulty stems from the multi-faceted and ambivalent aspect of the phenomenon which, like the complementarity between ἴς and βία in the Greek language, can be seen in Antiquity, depending on the point of view adopted, as an act of physical vigor or as an inacceptable constraint. To get a better understanding of this, this collection of articles sets out to study, not the violent act in itself, but rather the moments before and after, the goal being to understand the mechanics of violence. Focused on physical violence happening in the city, in the civic, religious or intimate spaces and drawing on textual, historical and iconographical analyses, this collection looks successively at the role of law, stasis, authority figures and, finally, speech in this process.